Recommended best management practices for Colorado green gentian (Frasera coloradensis): practices developed to reduce the impacts of road maintenance activities to plants of concern - Smith, Gabrielle, author; Panjabi, Susan Spackman, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2014)
Colorado green gentian (Frasera coloradensis) is a small plant in the Gentianaceae (Gentian Family) that is known only from the southeastern Colorado in Baca, Bent, Prowers, and Las Animas counties, and is considered to be imperiled at a global and state level (G2G3/S2S3; Colorado Natural Heritage Program 2014). One of the biggest conservation issues for this imperiled plant species is the lack of awareness of its existence and status. Avoiding or minimizing impacts to this species during road maintenance activities will effectively help to conserve its habitat and is unlikely to confer substantial impacts on road maintenance goals and projects. The Best Management Practices (BMPs) included in this document are intended to help increase the awareness of this species for anyone involved in road maintenance activities. The desired outcome of these recommended BMPs is to significantly reduce the impacts of road maintenance activities to the Colorado green gentian on federal, state, and private land. The BMPs listed here are intended to be iterative, and to evolve over time as additional information about the Colorado green gentian becomes available, or as road maintenance technologies develop. The intent of these BMPs is to inform people working along roadside areas regarding the importance of Colorado green gentian, one of Colorado's botanical treasures, and to outline some of the ways in which this species can coexist with road maintenance activities. The implementation of these recommendations will help to assure that maintenance activities proceed without unintended harm to the Colorado green gentian.
Prepared for: Colorado Department of Transportation and the Colorado Natural Areas Program.
May 2014.
Keywords: plant habitat; noxious weed management; Colorado green gentian; species profile